Nanomaterial-mediated antibiotic delivery: a novel strategy for osteomyelitis therapy - Cheng, Shuang; Meng, Xiao-Hui; Li, Zhi; Han, Hai-Hui; Zhang, Ya-Feng (Frontiers in Bioengineering and Biotechnology, 2025)
Osteomyelitis is an inflammatory bone disease caused by bacterial infection, often leading to bone destruction and functional impairment. Traditional treatments face significant limitations, including substantial surgical trauma, low drug delivery efficiency, and a high risk of recurrence. Nanomaterial-mediated antibiotic delivery has emerged as an innovative strategy, enabling localized, targeted and controlled antibiotic release. Representative platforms include nanohydroxyapatite (nHA), mesoporous bioactive glass (MBG), poly (lactic-co-glycolic acid) (PLGA), metal–organic frameworks (MOFs), silver nanoparticles (AgNPs), and multifunctional hybrid composites. This approach can enhance therapeutic efficacy, reduces systemic side effects, and promotes bone regeneration. This review summarizes the pathogenesis and therapeutic challenges of osteomyelitis, explores the construction and delivery mechanisms of nanocarriers, and discusses recent advances from in vitro studies to animal models and clinical research. Current evidence indicates that nanocarrier-based drug delivery systems can effectively inhibit bacterial growth, modulate inflammatory responses, and facilitate bone regeneration. However, their large-scale clinical application remains limited by concerns regarding safety, manufacturing complexity, regulatory standardization, and cost. Future directions include the development of intelligent nanocarriers, integration with multimodal therapeutic strategies (e.g., photothermal, immunomodulatory, and stem cell-assisted therapies), establishment of standardized multi-tier toxicity evaluation frameworks, and progression toward large-animal validation and early phase clinical trials, which are expected to drive further progress and provide more effective and safer treatment options for osteomyelitis.